Use of Routine-Based Instruction to Develop Object Perception Skills with Students Who Have Visual Impairments and Severe Intellectual Disabilities: Two Case Studies. (March 2020) - Smith, Mildred; Chambers, Stacey; Campbell, Angela; Pierce, Tristan; McCarthy, Tessa; Kostewicz, Douglas E.
Introduction: This article demonstrates the effectiveness of the use of routine-based instruction for teaching sensorimotor-stage object-perception skills to students who have visual impairments (i.e., blindness or low vision) and severe intellectual disabilities. Method: Classroom teachers documented progress toward achievement of object perception goals embedded in everyday instruction for two students.Results: Both students demonstrated higher levels of object-perception skills after 4 months of routine-based instruction. Discussion: The authors discuss the use of highly attractive sensory topics and the supports and accommodations used to increase sensory-efficient object engagement. Implications for practitioners: Routine-based instruction may accelerate progress in the development of object-perception skills in students whose present cognitive levels of performance are at the sensorimotor stage regardless of chronological age. Additional goals may include expanding object perception skills for additional objects in new routines that create coherence in multiple contexts.